UVB-induced bullous pemphigoid in a patient with psoriasis - Ceryn, Justyna; Skibińska, Małgorzata; Barasińska, Paulina; Noweta, Marcin; Narbutt, Joanna; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease affecting mostly elderly people. The clinical picture includes erythematous oedema, excoriated plaques and itchy tense blisters [1]. Drugs, infectious diseases, UV and X-ray radiation are described as some of the triggering factors in the development of the disease [2]. The diagnosis of BP is based on direct immunofluorescence examination (DIF). Typical clinical features, histopathological examination and positive indirect immunofluorescence (IIF) test may be helpful in confirming BP diagnosis. Coexistence of BP with psoriasis was first reported in 1929 by Bloom [3] and has been investigated since then. Several case reports, including phototherapy as a possible triggering factor, were published [4–6].